Nuclear irradiation-induced superconductivity in the binary semiconductor InAs - Kаrpenko, А.Ya.; Litovchenko, P.G.; Shevtsova, О.N.; Sugakov, V.I.; Vikhlii, G.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
A jump-like increase of the resistance as a function of magnetic field is observed in indium arsenide samples irradiated by a particles with an energy of 80 MeV. The effect is detected at T < 5 K. The observed effect is explained by the appearance in the crystal of superconducting areas createdby nuclear irradiation. The magnetoresistance is caused by suppression of the superconductivity inthe inclusions under magnetic field increase. The observed effect is considered in terms of a theory of the magnetoresistance of a medium with superconducting inclusions, proposed earlier. The proposed theory explains qualitatively the experimentally measured dependence of the resistance on magnetic field, namely: the jump of the resistance at a certain value of magnetic field; the shift of the curves towards higher magnetic fields with decrease of temperature; at lower values of the temperature the jump takes place in a wider range of magnetic fields (i.e., the curves became flatter).